2004
DOI: 10.3758/bf03196871
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating familiarity from recollection using rote rehearsal

Abstract: Recollection-based recognition memory judgments benefit greatly from effortful elaborative encoding, whereas familiarity-based judgments are much less sensitive to such manipulations. In this study, we have examined whether rote rehearsal under divided attention might produce the opposite dissociation, benefiting familiarity more than recollection. Subjects rehearsed word pairs during the "distractor" phase of a working memory span task, and were then given a surprise memory test for the distractor items at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
6
18
1
Order By: Relevance
“…As the Remember/Know paradigm has also been used to establish a dissociation of the effects of rehearsal, with elaborative rehearsal selectively affecting Remember responses and maintenance rehearsal selectively affecting Know responses (Dobbins et al 2004;Gardiner et al 1994;Gardiner and Richardson-Klavehn 2000), these findings also are consistent with the notion that the adults with AS engage in less elaborative rehearsal than TD adults. As yet, there is no conclusive evidence to link the episodic memory impairments in this population specifically to the rehearsal styles employed.…”
supporting
confidence: 67%
“…As the Remember/Know paradigm has also been used to establish a dissociation of the effects of rehearsal, with elaborative rehearsal selectively affecting Remember responses and maintenance rehearsal selectively affecting Know responses (Dobbins et al 2004;Gardiner et al 1994;Gardiner and Richardson-Klavehn 2000), these findings also are consistent with the notion that the adults with AS engage in less elaborative rehearsal than TD adults. As yet, there is no conclusive evidence to link the episodic memory impairments in this population specifically to the rehearsal styles employed.…”
supporting
confidence: 67%
“…The hemispheric asymmetry we observed is consistent with our hypothesis that reconstruction vs. distance processes are similar to recollection vs. familiarity processes, respectively, which have been previously associated with left vs. right PFC activations (Dobbins, Kroll, et al, 2004;Eldridge, et al, 2000;Henson, et al, 1999). For example, Henson et al (1999) used the "remember-know" procedure (Tulving, 1985) to determine when memory is accompanied by contextual details ("remember" judgment) versus when it is not ("know" judgment), as based on participant introspections.…”
Section: Hemispheric Asymmetry In Prefrontal Cortex Activitysupporting
confidence: 88%
“…The finding of right DL-PFC activity in association with long lags is consistent with functional neuroimaging evidence linking this region to familiarity (Dobbins, Kroll, & Yonelinas, 2004;Eldridge, et al, 2000;Henson, et al, 1999). A related interpretation of these right PFC activations is that they reflect an increase in monitoring for items that are close to the response criterion (Henson, et al, 2000).…”
Section: Regions Associated With Distance Processes During Longer Timsupporting
confidence: 82%
“…There were too few rehearse trials with two or three subsequently recollected items to conduct the same type of subsequent memory analysis that was performed for reorder trials (see supplemental material, available at www.jneurosci.org). This is not surprising, because previous studies have shown that rote maintenance rehearsal promotes memory performance primarily by building item strength in a manner that supports overall recognition, rather than recollection (Greene, 1987;Dobbins et al, 2004). We therefore investigated the relationship between prefrontal activity during the memory delay on rehearse trials and subsequent item recognition memory, collapsing across remember and know responses.…”
Section: Behavioral Resultsmentioning
confidence: 88%
“…Given that both WM maintenance (Greene, 1987;Dobbins et al, 2004; and organizational processing (Tulving and Pearlstone, 1966;Bower, 1970;Sternberg and Tulving, 1977;Hunt and Einstein, 1981;Davachi and Wagner, 2002) promote LTM formation, both DLPFC and VLPFC activity at encoding should be correlated with successful LTM performance. Figure 1 and Table 1 summarize results from functional magnetic resonance imaging (fMRI) studies that compared lateral prefrontal activity during encoding of items that were remembered on a subsequent memory test with activity elicited by subsequently forgotten items.…”
Section: Introductionmentioning
confidence: 99%